Allergic Bronchopulmonary Aspergillosis with an Atypical Mass-Like Presentation - Mahmoud Ibrahim Mahmoud; Alaeldin Elfaki; Ziad A. Alhaj; Abir Hamad Said (Case Reports in Pulmonology)
Allergic bronchopulmonary aspergillosis is an uncommon condition characterized by airway hypersensitivity to Aspergillus fumigatus, resulting in worsening asthma control and bronchiectasis progression. It is associated with various radiological features. Here, we describe a 53-year-old lady with atypical CT chest finding as soft tissue density masses in both lungs evaluated initially as a lung tumour. The diagnosis was particularly challenging given the history of undiagnosed asthma. Nevertheless, bronchoscopy findings of mucus impaction and blood eosinophilia redirect the clinical thinking toward ABPA. Laboratory examination showed elevated total IgE, Aspergillus fumigatus IgE, and Aspergillus niger IgE. Shortly after treatments with systemic steroids, our patient showed a symptomatic improvement. Moreover, subsequent follow-up showed a resolution of the radiological opacities.